Determine the Physical-Chemical, Bacteriology Properties and Heavy Metals in Tap Water vs. Bottle Water in Duhok Governorate - Dosky, Ali H.Al- (Journal of Neonatal Surgery, 2025)
Background: The development and spread of tap water systems over the past century have transformed the world by making clean water available to billions of people who would otherwise have continued to suffer all the health and development problems caused by clean water scarcity of centuries past. Bottled water is defined by the United States Food and Drug Administration (FDA) as “water that is intended for human consumption and sealed in bottles or other containers with no added ingredients, except that it may contain a safe and suitable antimicrobial agent as well as limited levels of fluoride.” Objective -To determine the physical-chemical, bacteriology properties and heavy metals in tap water vs. bottle water. -To find relationship between physical, chemical, heavy metals and bacteriological properties in tap water vs. bottle water. Methods: A descriptive and analytic study for (200) random sample divide two part (100) sample from Tap water distributed in different regions and (100) sample from ten factories products. The study included test for temperature, pH, physical, and chemical tests, heavy metal, and bacteriology. Conclusion: The temperature, pH, physical, chemical, bacteriology tests, and heavy metal, on samples taken from their place and production factories must be in conformity with international standards, and this is due to the importance of water in life. Recommendation: The study recommended that health education can be conveyed through the mass media by television, documentaries, brochures, posters, and educational programs which aim to raise awareness of people in all religion s of d Duhok Governorate. Results: The chemical examination for the all parameter for the tap water, it has shown in table -1. The heavy metal examination for the all parameter for the tap water, it has shown in table -2. The bacteriological examination for the all sample of the tap water, it has shown in table -3. The chemical examination for the all parameter for the bottled water, it has shown in table -4. The heavy metal examination for the all parameter for the tap water, it has shown in table -5. The bacteriological examination for the all sample of the bottle water, it has shown in table -6. The chemical examination result for the all parameter between tap water vs bottle water as shown in the table 7 and figure 1. The heavy metal examination result for all parameter between tap water vs bottle water as shown in table 8 and figure 2.